1997
DOI: 10.1016/s0005-2728(97)00055-8
|View full text |Cite
|
Sign up to set email alerts
|

Preferential oxidation of cardiac mitochondrial DNA following acute intoxication with doxorubicin

Abstract: The purpose of this investigation was to determine whether acute doxorubicin intoxication causes a preferential accumulation of 8-hydroxydeoxyguanosine (8OHdG) adducts to mitochondrial DNA (mtDNA) as opposed to nuclear DNA (nDNA), particularly in cardiac tissue. Adult male rats received a single i.p. bolus of doxorubicin (15 mg/kg) and were killed 1-14 days later. Acute intoxication with doxorubicin caused a 2-fold greater increase in 8OHdG adducts to mtDNA compared to nDNA, the concentration of adducts to bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 36 publications
1
47
1
1
Order By: Relevance
“…Experiments with human hepatic cell lines also showed that almost half of the metal accumulates in the mitochondria where it causes ultrastructural alterations, as observed by transmission electron microscopy [40]. Most of the bioenergetic experiments with Hg report the uncoupling of oxidative phosphorylation [72], inhibition of ATP synthesis [10], impairment of the respiratory chain [58] and depletion of intracellular ATP and ADP [55]. A study using a selective probe for mitochondrial reactive oxygen intermediates as well as other probes demonstrated a significant MeHg-induced increase in intracellular superoxide anion, hydrogen peroxide and hydroxyl radicals, indicating that the mitochondrial electron transport chain is an early, primary site for ROS formation [2,65,66,74].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with human hepatic cell lines also showed that almost half of the metal accumulates in the mitochondria where it causes ultrastructural alterations, as observed by transmission electron microscopy [40]. Most of the bioenergetic experiments with Hg report the uncoupling of oxidative phosphorylation [72], inhibition of ATP synthesis [10], impairment of the respiratory chain [58] and depletion of intracellular ATP and ADP [55]. A study using a selective probe for mitochondrial reactive oxygen intermediates as well as other probes demonstrated a significant MeHg-induced increase in intracellular superoxide anion, hydrogen peroxide and hydroxyl radicals, indicating that the mitochondrial electron transport chain is an early, primary site for ROS formation [2,65,66,74].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that DOX had high affinity for cardiolipin, the phospholipid in the inner mitochondrial membrane [24] . This affinity results in the accumulation of DOX in cardiac myocytes with higher concentrations than that in other cells [25] , and causes oxidative damage on mitochondrial membranes, the respiratory chain, and DNA [26][27][28] . On the other hand, the mitochondrial respiratory chain is the major source of superoxide, thus, mitochondria are more susceptible to oxidative damage than the rest of the cells [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies strongly support reactive species as playing a prominent role in mtDNA deletions through oxidative damage. Under conditions of oxidative stress, accumulation of signifi cantly higher levels of DNA oxidation product 8-hydroxydeoxyguanosine in mtDNA compared to nuclear DNA and increased degradation of the mutated mtDNA is shown in a variety of in vitro and in vivo conditions (Palmeira et al 1997, Williams et al 1998, Serrano et al 1999. It is postulated that increased ROS production may lead to mutations and eventually degradation of oxidatively damaged mtDNA, thus accounting for decreased assembly and activity of respiratory complexes in chagasic myocardium.…”
Section: Factors Contributing To Mitochondrial Dysfunctionmentioning
confidence: 99%